Gastrointestinal Subepithelial Lesions: A Review - Pal, Sandip; Hodgar, Digvijay (Journal of Digestive Endoscopy, 2023)
Submucosal lesions, also known as subepithelial lesions, are often encountered during endoscopy of the gastrointestinal tract. Most of the lesions are asymptomatic and can be diagnosed by routine endoscopic ultrasonography. Few lesions like gastrointestinal submucosal tumors (GIST) and leiomyoma require biopsy/fine-needle aspiration cytology (FNAC) for differentiation. Lesions like neuroendocrine tumors can be diagnosed by deep endoscopic biopsy as they originate from the inner mucosal layer. Management depends on the size and layer of origin of the lesion. Smaller lesions can be removed by endoscopic procedures and bigger lesions by surgery. Smaller lesions can be safely surveilled.
Keywords: endoscopic ultrasonography; gastrointestinal stromal tumors; leiomyoma; neuroendocrine neoplasm; subepithelial lesions